Determination of oligoelements in parenteral formulations by planar chromatography and spectrophotometry - Mancini, MAD; Netto, J. Z. (Marcel Dekker Inc, 1998)
The authors have studied the chromatographic behavior of parenteral preparations for pediatric use containing inorganic cations. After separation and identification by thin-layer chromatography, Mn2+, Zn2+, and Cu2+ were analyzed by a method based on reaction with an appropriate reagent and extraction with an organic solvent which yielded elution and preconcentration, resulting in an appropriate solution for colorimetric quantitation. Cr3+ cation was determined by atomic absorption spectrophotometry after appropriate chromatographic separation, using microcrystalline cellulose (adsorbent) and an acetone:water:hydrochloric acid mixture (80:5:8) as the mobile phase.